Monte Carlo simulations study on gamma ray-neutron shielding characteristics for vinyl ester composites - KARTAL, İLYAS (WILEY, 2021)
The current study aims to report the gamma ray-neutron attenuation parameters of eight types of vinyl ester pumice (V-P) composites for wide energy ranges of 511-2140 keV via MCNPX and FLUKA codes. The radiation shielding properties of these composites were presented graphically and are discussed in detail in this study. From the obtained results, it can be concluded that the MCNPX and FLUKA outcomes are in agreement with each other, and also the FLUKA code can be used as an alternative technique to determine the attenuation features of vinyl ester composites. Besides, the linear attenuation coefficient and total macroscopic cross sections' ( n-ary sumation (t)) dependencies on the density and also mass attenuation coefficient were found for all selected samples. To sum up, findings show that composite coded as V-P50 can be a good competitive candidate in terms of gamma rays and neutron shielding.
Keywords: gamma-neutron attenuation features; MCNPX and FLUKA simulations; vinyl ester composite; NATURAL RADIOACTIVITY LEVELS; AUTOCLAVED AERATED CONCRETE; LIFETIME CANCER-RISK; ATTENUATION COEFFICIENTS; PARAMETERS; SAMPLES; REGION